Cytotoxic Activity on Brine Shrimp, MCF-7 Cell Line and Thrombolytic Potential: Seven Different Medicinal Plant Leaves Extract - Azad, A. K.; Jainul, M. A.; Labu, Z. K. (Journal of Scientific Research, 2018)
The aim of our study was to find out the preliminary cytotoxic and thrombolytic effect of the seven selected medicinal plant leaves extract. In cytotoxic activity, out of the seven leaves extract three of them exhibited stronger brine shrimp lethality with LC50 122.548 (Uncaria acida), 170.861 (Leea indica) and 175.469 (Piper porphyrophyllum) μg /mL respectively, and on MCF-7 cell line, they also exhibited moderate cytotoxic activity with different concentration of the extract of the same plant leaves such as,Uncaria acida (72.31, 56.22, 38.12 and 9.24%), Leea indica (67.31, 58.22, 43.12 and 15.24%), Piper porphyrophyllum (65.88, 48.12, 40.12 and 21.34%). In thrombolytic assessments, all the leaves extract showed moderate (considering > 20% moderate; **p < 0.01; *p < 0.05) clot lysis activity, but among the extracts, Uncaria cordata (27.36 ± 0.10%) showed the highest and Stachytarpheta indica the lowest (6.14 ± 0.20%) percent clot lysis as compared with the standard streptokinase (65.15 ± 0.16%). This study was conducted to legalize the folkloric use of seven medicinal plant leaves.